1977
DOI: 10.1007/bf00626278
|View full text |Cite
|
Sign up to set email alerts
|

Venous drainage in the craniocervical region

Abstract: The venous drainage of the craniocervical junction is made up of jugular veins and particularly the vertebral veins and their anastomoses. The anterior and posterior condylar veins join to form the plexus of the vertebral vein, the supply functions of which can be modified by the presence of the mastoid anastomotic emissary veins which increase the possibilities of drainage at that level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…It communicates with the internal jugular vein, with the vertebral venous plexus and the clival venous plexus through multiple small channels 18 . In about 2% of patients, the OS behaves as a major drainage channel to the straight sinus or SSS 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…It communicates with the internal jugular vein, with the vertebral venous plexus and the clival venous plexus through multiple small channels 18 . In about 2% of patients, the OS behaves as a major drainage channel to the straight sinus or SSS 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…cervical venous plexus [21][22][23] especially when, like in our case, the right internal jugular is closed and there is not an anti-siphon system .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 46%
“…The mastoid emissary vein arises from the middle portion of the sigmoid sinus and joins the posterior auricular vein, the occipital vein or the deep cervical vein (Fig. 4) [3][4][5]. In a recent study, the mastoid emissary vein was found in 63% of the evaluated mastoids [4].…”
Section: Discussionmentioning
confidence: 99%